Prognosis of Adverse Outcomes in the Research of Coronary Blood Flow During Echocardiography - E. S. Kalinina; A. V. Zagatina; S. A. Sayganov (Столичная издательская компания, 2023)
Aim. The goals of this research are to define the frequency of the coronary arteries visualization possibilities depending on various factors at routine echocardiography and estimate to the relation of coronary flow ultrasound parameters to prognosis of the adverse outcomes in the subsequent year.Material and methods. The study comprises 581 consecutive patients. All patients performed echocardiography following standard method with an additional tab called «Coronary» which was set to visualize coronary arteries. Also all patients underwent a standard examination and debriefing of anamnesis. Observation of patients was the next year after echocardiography. The end points in the study - death from any cause, myocardial infarction (MI), death/ MI, myocardial revascularization operations - stenting and aortocoronary bypass (CABG). The analysis of clinical outcomes was carried out using the study of medical history and outpatient cards, interviewing patients at the time of admission, as well as the method of telephone survey of patients or their next of kin. ROC analysis as well as subgroup survival analysis using the Kaplan-Meier method was performed.Results. The possibility to visualize the segments of coronary arteries and to estimate the coronary flow was in 91% of cases, or 526 patients. Women predominated among the patients (59.7% versus 40.3%). During follow-up, 73 patients recorded endpoints: 23 people died, 4 patients suffered non-fatal MI. 24 patients underwent CABG, 22 patients - myocardial revascularization. Depending on the quartile distribution by body mass index and age, a significant difference in visualization was not identified. Mortality was observed significantly more frequent when the flow velocity in the left coronary artery/proximal left artery descending/circumflex artery was higher than 64 cm/s. Flow velocity in left coronary artery /proximal left artery descending 64 cm/s was the cut-off value predicting MI with 100% sensitivity, 73,4% specificity (p<0.0001). Conclusion. Coronary flow velocity parameters provide long-term prognostic value that can be used to identify individuals with high risk of developing adverse cardiovascular events. Key words: coronary flow velocity, echocardiography, coronary artery, adverse events>˂0.0001).Conclusion. Coronary flow velocity parameters provide long-term prognostic value that can be used to identify individuals with high risk of developing adverse cardiovascular events.